Should We Accept Arguments from Skeptics to Ignore the Psi Data? A Comment on Reber and Alcock’s Searching for the Impossible - Williams III, George Robert (Journal of Scientific Exploration, 2019)
Reber and Alcock have recently made a sharp attack on the entire psi literature, and in particular a recent overview by Cardeña of the meta-analyses across various categories of psi. They claim the data is inherently flawed because of its disconnect with our current understanding of the world. As a result, they ignore the data and identify key scientific principles that they argue clash with psi. In my paper, I argue that these key principles are difficult to apply in areas where our understanding remains poor, especially quantum mechanics and consciousness. I also explore how the psi data may fit within these two areas.